Marketing Management Study Program in the Era of Digital Economy and Green Economy - Teddy Rochendi (Journal of Social Research, 2023)
It is easy to see that the implementation of higher education today is moving into an industry. The higher education service industry that shifts the meaning of the noble ideal of educational goals is to humanize people. The method used in this study is a qualitative method by collecting data, reading and recording, and managing it. The convenience offered in the Digital Economy automatically opens up wide business opportunities in various fields. The management of Tiggi University must be able to synergize all potentials in various situations and various stakeholders in collaborative cooperation between the government, business actors, and other parties. In a digital economy practice situation, the key to a university's success in marketing its study program lies in the level of ability and quality of managers in bringing together three important factors, namely: computing, communications, and content. Computing, which is the core of the industry, computing is the center of data and information processing needed to carry out Tri Dharma transactions.